Preparation method of force-heat-light multifunctional fusion alloy
By doping Ta elements into NiTi-based alloys and preparing ultrafine grain alloys, combining FIB technology to process horseshoe-shaped metasurface and hydrogel composites, the shortcomings of NiTi-based alloys in multifunctional integration are solved, and the multifunctional fusion of force-thermal and light is achieved, and the comprehensive performance of the material is improved.
Patent Information
- Application Number
- CN202411996585.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
Existing NiTi-based alloys have significant shortcomings in multifunctional integration, especially in the coordinated optimization of thermal response and optical characteristics.
Ultrafine grain alloys are prepared by doping Ta elements in NiTi-based alloys and vacuum smelting and water-cooled copper mold solidification technology. Then, horseshoe-shaped metasurface is processed by FIB technology, and finally combined with thermal insulation and heat absorption hydrogel.
The multifunctional fusion of the NiTi-based alloy is realized, improving the thermal phase transformation, shape memory effect, optical regulation ability, as well as high temperature stability and strength of the material.
Smart Images

Figure CN119800132A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of intersection of metal materials and functional materials, and in particular to a method for preparing a mechanical, thermal and optical multifunctional fusion alloy. Background Art
[0002] With the rapid development of the field of smart materials, multifunctional alloys have become a research hotspot due to their excellent comprehensive properties and wide application potential. Among them, NiTi-based alloys are widely used in biomedicine, aerospace, consumer electronics, and high-precision sensors due to their unique shape memory effect and superelastic behavior. However, existing NiTi-based materials perform well in a single performance, but still have significant deficiencies in multifunctional integration. For example, most NiTi alloys only focus on the shape memory effect, while ignoring the synergistic optimization between their thermal responsiveness and optical properties.
[0003] In extreme environments (such as high temperature, high light radiation or mechanical stress field), the functional integration of materials is particularly important. To meet this demand, it is urgent to develop a multifunctional NiTi-based alloy that can simultaneously possess high strength, thermal phase change, shape memory function and optical regulation capabilities. This type of material can not only transmit signals through thermal phase change, but also adjust the reflection and absorption rate of light at different temperatures, thereby achieving a high degree of integration of multi-field coupling functions. This kind of force-heat-light multifunctional fusion material has important application value in the fields of intelligent sensing, optical control and efficient energy conversion. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method of a mechanical, thermal and optical multifunctional fusion alloy. Taking NiTi-based alloy as the research object, based on alloy composition design and microstructure optimization, starting from theoretical analysis, experimental verification and parameter control, a new mechanical, thermal and optical fusion alloy is developed to solve the technical bottleneck of traditional NiTi-based alloy materials in multifunctional synergy.
[0005] To achieve the above object, the present invention provides a method for preparing a mechanical, thermal and optical multifunctional fusion alloy, which specifically comprises the following steps:
[0006] S1. Mix metal elements Ni, Ti and Ta;
[0007] S2, the Ni, Ti, Ta metal elements in S1 are placed in a vacuum arc melting furnace for melting to obtain cast NiTiTa 0.2 alloy;
[0008] S3, the cast NiTiTa obtained in S2 0.2 The alloy is melted and then directionally solidified using a water-cooled copper module to obtain ultra-fine-grained NiTiTa 0.2 alloy;
[0009] S4, NiTiTa obtained in S3 by FIB technology 0.2 A horseshoe-shaped metasurface with a matrix etched on the alloy;
[0010] S5, NiTiTa obtained in S4 0.2 The base layer of the alloy is compounded with the heat-insulating and heat-absorbing water gel to obtain a multifunctional fusion alloy.
[0011] Preferably, in S1, the atomic ratio of the metal elements Ni, Ti and Ta is 1:1:0.2, and the purity of Ni, Ti and Ta is greater than 99.9%.
[0012] Preferably, in S2, Ni, Ti, and Ta metal single substances are melted in an argon atmosphere, and the melt is stirred by magnetic drive.
[0013] Preferably, in S3, the cast NiTiTa 0.2 The alloy was melted in an argon atmosphere.
[0014] Preferably, in S4, the opening angle of the horseshoe is 20-60°.
[0015] Preferably, in S4, the matrix array is composed of 10×10 horseshoe-shaped units, the diameter of the horseshoe-shaped unit is 500 nm, the opening width is 100-500 nm, and the spacing between adjacent horseshoe-shaped units is 1000 nm.
[0016] Preferably, in S5, the heat insulating and heat absorbing hydrogel is a borate cross-linked hydrogel.
[0017] Preferably, in S5, the content of water molecules in the heat-insulating and heat-absorbing water gel is 70%.
[0018] A unique crystallographic property of NiTi alloy is the martensitic phase transformation.
[0019] As one of the main components, Ni plays a key role in NiTi alloys and provides a basis for the realization of shape memory effect, which is manifested as the alloy recovering to its original shape through temperature change after plastic deformation. The role of Ni in this effect is mainly reflected in the following aspects: regulating the crystal structure, promoting the reversible phase transformation process between austenite (B2) and martensite (B19'), improving material performance and optimizing defect structure. The shape memory effect of NiTi alloy depends on its reversible martensitic phase transformation, which is specifically manifested as the transformation of crystal structure under different temperature conditions. The high-temperature phase (austenite phase) has a B2 cubic structure and strong mechanical rigidity, which is the memory state of the material. The low-temperature phase (martensite phase) presents a B19' monoclinic structure, which allows large reversible deformation and is the realization state of shape memory. The presence of Ni plays a decisive role in the stability and phase transformation temperature of the above structure. The Ni content has a significant effect on the driving force of the phase transformation of martensite and austenite. When the Ni content is moderate (about 50% atomic percentage), the material exhibits ideal phase transformation characteristics and the shape memory effect is maximized. If the Ni content is too high (e.g. >51%), the phase transition temperature will decrease, the austenite phase will be more stable, and the shape memory effect may be weakened. If the Ni content is too low (e.g. <49%), the martensite phase transition temperature will increase, and the phase transition kinetics of the material will be limited.
[0020] The key role of Ni in NiTi alloy is also reflected in its promotion of the martensitic phase transformation mechanism. The essence of the shape memory effect is driven by the reversible phase transformation between austenite and martensite: in the cooling stage, the temperature decreases and NiTi transforms from the high-temperature austenite phase (B2) to the low-temperature martensite phase (B19'). In this process, Ni atoms provide a stable lattice arrangement, endowing the material with reversible deformation ability and supporting the orderly reorganization of the austenite structure into the martensite structure. The martensite phase has a high lattice variability, allowing the alloy to produce reversible lattice deformation under the action of external force without causing permanent damage. In the heating stage, when the temperature rises to a specific value of the austenite start temperature or the completion temperature, the martensite phase in the NiTi alloy will transform back into the austenite phase and restore the original shape; in this process, the free electron effect provided by Ni drives the martensite to transform into austenite and restore the original shape. At the same time, the free electrons provided by Ni enhance the alloy bonding, making the thermodynamic stability of the austenite phase higher. In addition, the presence of Ni enables the NiTi alloy to maintain stable phase change behavior during loading and unloading cycles, significantly improving the reversibility and durability of its shape memory effect.
[0021] The role of Ni is not limited to phase transformation regulation, but also significantly improves the mechanical and functional properties of NiTi alloys, while optimizing the defect structure. Ni provides additional free electrons, strengthens the metal bonds of the alloy, and enables NiTi to withstand greater stress during loading without causing permanent deformation. In the superelastic state (above the martensitic phase transition temperature), the electronic effect of Ni enables the alloy to exhibit significant elastic deformation capabilities and recover quickly after unloading. This superelastic property has important application value in orthopedic implants, dental instruments and other fields.
[0022] During material processing, excessive Ti or Ni will lead to the formation of secondary phases such as Ti2Ni or Ni3Ti at the grain boundaries. These brittle phases will significantly weaken the shape memory effect and mechanical properties of the material. An appropriate amount of Ni can inhibit the formation of excess Ti phase and optimize the crystal defect structure of the alloy. At the same time, the uniform distribution of Ni atoms can also reduce the dislocation density and optimize the crystal defect structure, thereby enhancing the stability and service life of the alloy and further improving the reversibility of the phase change process.
[0023] Ti plays a core role in strength and phase stability in NiTi alloys. In NiTi alloys, the atomic properties and crystallographic behavior of Ti directly affect the microstructure, mechanical properties and phase transformation kinetics of NiTi alloys. NiTi alloys have high strength, which is partly attributed to the solid solution strengthening and microstructure optimization effects of Ti in the lattice. In NiTi alloys, Ti atoms significantly enhance the bonding force of the crystal structure by forming strong metallic bonds with Ni atoms. This effect stems from the larger atomic radius (compared to Ni) and lower electron density of Ti atoms. The presence of Ti can cause lattice distortion, increase the difficulty of dislocation movement, and thus improve the yield strength and tensile strength of the alloy. The solid solution strengthening effect caused is particularly significant in the martensite phase (B19' structure), which improves the strength of the material at low temperatures by enhancing the deformation resistance of the crystal.
[0024] Under certain processing conditions, Ti may be present as Ti2Ni or Ti4Ni2O x The precipitation of Ti and other secondary phases, which are distributed inside the grains or on the grain boundaries, can further improve the strength of the alloy: the appropriate amount of Ti precipitation phase can effectively hinder the slip of dislocations and the migration of grain boundaries, thereby improving the yield strength and fatigue resistance of the alloy. The appropriate amount of Ti precipitation phase can also pin the creep behavior under high temperature conditions and extend the service life of the material.
[0025] The addition of Ti is also crucial to the control of the grain size of the NiTi alloy. A higher Ti content will promote the formation of fine grains during casting or heat treatment, and the grain refinement effect helps to enhance the strength and toughness of the material. The Ti content directly affects the key phase transformation parameters of the NiTi alloy, such as the martensite start temperature and the austenite finish temperature: when the Ti content increases (within an appropriate range), the martensite phase stability of the alloy is enhanced, allowing it to undergo a martensite phase transformation at a lower temperature. This is especially important for applications in low temperature environments (such as spacecraft components). The chemical bond strength of Ti has a positive effect on the resistance of the martensite phase to thermal disturbances, and improves the reversibility and stability of the phase transformation.
[0026] Ti can significantly improve the stability of the high-temperature austenite phase in NiTi alloys: at higher temperatures (such as working conditions in industrial applications), Ti forms stronger B2 austenite crystal bonds with Ni, improving the material's resistance to external thermal disturbances, thereby avoiding performance degradation at high temperatures. And by affecting the composition distribution of grain boundaries, the trend of austenite transforming to a brittle phase (such as Ni3Ti) is suppressed. The segregation behavior in the grain boundary region can also improve the phase stability of NiTi alloys. By refining the grain boundaries, Ti effectively reduces the grain boundary energy, thereby enhancing the material's resistance to external forces and temperature changes, allowing NiTi alloys to exhibit higher fatigue life and lower crack growth rates under cyclic loading conditions.
[0027] The strengthening effect of Ti is not only reflected in the mechanical properties, but also in the coordinated optimization of mechanical properties and functional characteristics by regulating the phase transformation mechanism: the reversible deformation ability of the martensite phase is the basis of the shape memory effect. Ti provides a strong metallic bond in the crystal, allowing the martensite structure to withstand large deformation under external force without permanent damage. This property improves the reusability of the material.
[0028] The presence of Ti can effectively reduce the hysteresis phenomenon in the austenite-martensite phase transformation and improve the dynamic performance of the phase transformation. This feature is particularly important for high-frequency thermal cycling applications (such as actuators, lasers, etc.). The right amount of Ti can also reduce the amount of residual martensite after multiple phase transformations and improve the thermal cycle life of the material. In cyclic loading or high stress environments, Ti reduces the microstructural damage rate of the material by inhibiting dislocation movement and grain boundary sliding, making the NiTi alloy have excellent stability and durability in complex environments.
[0029] Ta doping plays a core role in the strength and phase stability of NiTi alloys. The high-temperature performance of NiTi alloys is an important factor in determining their application areas, especially in aerospace and energy engineering, where materials need to work for a long time under extreme temperature conditions. Ta doping significantly improves the melting point and high-temperature stability of NiTi alloys through the following mechanisms: Ta has a large atomic radius and a high melting point (3290°C). When it is doped into NiTi alloys, it forms strong metallic bonds in the crystal structure and produces a significant solid solution strengthening effect on Ni and Ti atoms. This effect increases the bond energy of the NiTi alloy crystal, making it more difficult for the material to undergo atomic diffusion and lattice collapse at high temperatures, thereby increasing its melting point.
[0030] Ta is prone to segregation at grain boundaries, significantly reducing grain boundary energy, inhibiting the rapid growth of grains at high temperatures, and changing the thermodynamic stability of the high-temperature austenite phase (B2) in NiTi alloys, thereby allowing the austenite phase to maintain good stability at higher temperatures. This effect is particularly important in applications that require high-temperature actuation or high-temperature shape memory functions.
[0031] The light reflection performance of NiTi alloy is crucial for the application of optical functional materials, and doping with Ta significantly improves its reflection ability in the infrared and visible light bands. As a transition metal, Ta has a complex electronic structure, and doping can effectively increase the free electron density of NiTi alloy. The increase in free electrons enhances the alloy's ability to reflect light, especially in the near-infrared band. In addition, Ta doping tends to improve the surface microstructure and flatness of NiTi, making its surface smoother and denser, thereby reducing light scattering and enhancing the reflection efficiency in the infrared and visible light bands. In addition, Ta generates stable oxides containing Ta (such as Ta2O5) by changing the composition of the surface oxide layer. Ta2O5 not only has high reflectivity, but also exhibits extremely strong corrosion resistance. This stable surface layer can maintain high reflectivity for a long time in an optical environment, avoiding performance degradation caused by chemical or environmental factors.
[0032] Ta doping can change the electronic band structure of NiTi alloy, thereby adjusting its absorption characteristics for light of different wavelengths. For example, the presence of Ta can enhance the absorption capacity of the alloy in the near-infrared and mid-infrared bands, making it suitable for the fields of solar heat collection and thermal radiation management. Under the preparation conditions of the present application, Ta doping will form nanoscale Ta-based phases (such as TaNi or TaC) on the surface or inside of the NiTi alloy. These nanostructures have a high surface area, can effectively capture incident light, and significantly improve the light absorption efficiency of the material. This feature is particularly suitable for scenes that require high light absorption rates, such as optoelectronic devices or laser ablation materials.
[0033] The present invention uses vacuum melting to repeatedly melt Ni, Ti and Ta five times to ensure uniform composition, and then obtains ultrafine grain NiTiTa by copper mold condensation technology. 0.2 Alloy. Then, the ultrafine grain NiTiTa 0.2 The alloy was cut into a horseshoe-shaped metasurface (10×10 array), and the optical scattering properties of the alloy were precisely controlled by the size and direction of the openings. This process enables a high degree of controllability of light scattering behavior by designing the geometric parameters of the metasurface structure (such as the size and direction of the openings). Adding a small amount of Ta can refine the grain structure while improving the strength and toughness of the material. The ultrafine grain structure further improves the surface quality and FIB processing adaptability of the material. Ta doping significantly optimizes the optical reflection and scattering properties of the alloy, making it an ideal substrate for optical metasurface materials.
[0034] FIB technology shows extremely high flexibility and precision in micro-nanoscale processing, and is particularly suitable for the preparation of complex geometric shapes: it can achieve shape-controlled cutting, engraving and hole processing at the nanoscale. The surface roughness generated during the processing is low, which is beneficial to improving the optical performance of the metasurface. The size and direction of the horseshoe opening can be precisely controlled by real-time regulation of the beam intensity and scanning path. Design principle of horseshoe metasurface design and array processing. The horseshoe structure is an asymmetric metasurface design, and its opening part can significantly affect the light scattering characteristics. The opening size affects the wavelength selectivity of the scattered light. Larger opening sizes tend to enhance the scattering of long-wavelength light, while small openings are more suitable for short-wavelength manipulation. The opening direction is conducive to adjusting the angular distribution of scattered light, and the arrangement in a specific direction can achieve polarization selectivity and directional scattering of light. The array consists of 10×10 horseshoe-shaped units with a diameter of 500nm, periodically arranged on NiTiTa 0.2 The 1000nm unit spacing design avoids interference between optical scattering. The size range of each horseshoe-shaped unit is adjustable (for example, the opening width is between 100-500nm) to meet the optical requirements in different wavelength ranges.
[0035] By adjusting the geometric parameters of the horseshoe structure, the scattering properties of the metasurface for light can be highly controllable. The larger the opening, the more the scattering center wavelength shifts toward the long-wave direction, which is suitable for mid-infrared band applications. The smaller the opening, the more the scattering center wavelength shifts toward the short-wave direction, which is more suitable for ultraviolet and visible light band manipulation. This mechanism stems from the regulatory effect of the opening size on the localized surface plasmon resonance (LSPR) mode. When the opening direction is consistent, the scattered light is concentrated within a specific angle range, showing enhanced directionality. If the opening direction is randomized, the scattered light distribution tends to be uniform, which can be used for diffuse reflection applications. This directional dependence enables the horseshoe metasurface to achieve polarization-selective scattering, which is suitable for polarized light detection or optical filtering devices. Reasonable design of the array period can introduce structural light interference effects, further enhancing the scattering intensity of specific bands or suppressing unnecessary band scattering. Optimizing light scattering efficiency over a wide spectral range can enhance the versatility of the metasurface.
[0036] Horseshoe-shaped metasurface NiTiTa 0.2 The alloy substrate and the heat-insulating and heat-absorbing water gel are combined to achieve multifunctional protection and dynamic optical regulation.
[0037] NiTiTa 0.2 The alloy substrate has high stability and thermal conductivity, provides mechanical strength and environmental corrosion resistance, and ensures the reliability of the material under extreme temperature conditions. The horseshoe-shaped metasurface regulates the optical scattering and absorption properties of NiTiTa 0.2 The substrate can effectively control the distribution of thermal energy, and the heat-insulating and heat-absorbing hydrogel assists in achieving its heat-insulating and heat-absorbing functions with components. Hydrogel is a functional material with high water content, flexibility and controllability. The evaporation and heat-absorbing properties of water molecules in the hydrogel can reduce the transfer of external heat to electronic devices, thereby forming an effective insulation layer. The content and distribution of water molecules in the hydrogel have a significant effect on the refractive index and absorptivity of light, and can achieve real-time dynamic adjustment of optical responses. At the same time, the hydrogel layer can serve as a flexible barrier to reduce the impact of external mechanical shock on the substrate and the electronic devices it carries. NiTiTa 0.2 The hydrogel layer is fixed on the surface of the alloy substrate by chemical bonding or physical adsorption, ensuring that the composite material has long-term stability and good interface bonding performance. The metasurface of the alloy substrate can control the scattering and absorption of infrared and visible light, reflecting part of the heat energy to the external environment and reducing heat accumulation. However, the thermal conductivity of the alloy is relatively fast, and the heat absorption capacity of water molecules in the hydrogel enhances the thermal insulation performance, which is especially suitable for electronic devices that require efficient thermal management. The heat absorption characteristics of the hydrogel in a high temperature environment help to regulate the overall thermal energy distribution of the system.
[0038] In summary, in the multifunctional alloy prepared by the present invention, Ni provides the shape memory effect of the martensitic phase transformation, Ti improves the strength and phase stability, and doping with the Ta element optimizes the optical properties of the alloy, increases the melting point, and improves the light reflection and absorption capabilities. Then, the strength and toughness of the material are improved by refining the grains. The opening size and direction of the horseshoe structure affect the scattering behavior of light. Large-sized openings enhance the scattering of long-wave light, and small-sized openings adapt to short-wave light manipulation. The opening direction controls the polarization and directionality of the scattered light, which can optimize the optical performance and adapt to the needs of different bands. In addition, the array design and periodic arrangement avoid optical scattering interference, and efficient scattering of light can be achieved by adjusting the geometric parameters, thereby improving the multifunctionality of the metasurface. NiTiTa 0.2 The alloy substrate provides high stability, thermal conductivity and corrosion resistance, ensuring reliability at extreme temperatures. The hydrogel reduces external heat transfer through heat absorption characteristics and adjusts the optical response to achieve heat insulation and heat absorption functions. The hydrogel layer can also mitigate external mechanical impact and enhance interface stability. The hydrogel layer is fixed on the surface of the alloy substrate to ensure long-term stability, and the scattering and absorption of infrared and visible light are controlled through the metasurface to optimize thermal energy management, which is particularly suitable for efficient thermal management of electronic devices.
[0039] Therefore, the present invention provides a method for preparing a multifunctional fusion alloy of force, heat and light, using Ta to increase the melting point of NiTi alloy, and using the shape memory characteristics caused by the thermal phase change of NiTi alloy to customize the microscale super surface to achieve optical asymmetry. At the same time, a hydrogel with excellent heat absorption and heat insulation capabilities is used as a composite substrate of the alloy, and the protective effect of the overall material is dynamically controlled by changing the content of water molecules in the hydrogel, so as to achieve protection of electronic devices against laser irradiation and thermal damage.
[0040] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a schematic flow chart of a method for preparing a mechanical, thermal and optical multifunctional fusion alloy of the present invention;
[0042] Figure 2 Copper mold cooling NiTiTa prepared in the embodiment of the present invention 0.2 Overall morphology of the alloy;
[0043] Figure 3 Copper mold cooling NiTiTa prepared in the embodiment of the present invention 0.2 Microscopic morphology of the alloy;
[0044] Figure 4 Copper mold cooling NiTiTa prepared in the embodiment of the present invention 0.2 The horseshoe-shaped supersurface morphology obtained by FIB processing of the alloy;
[0045] Figure 5 Copper mold cooling NiTiTa prepared in the embodiment of the present invention 0.2 Characterization diagram of the composite interface between the alloy substrate bottom layer and the heat-insulating and heat-absorbing water gel;
[0046] Figure 6 Copper mold cooling NiTiTa prepared in the embodiment of the present invention 0.2 Comparative DSC curves of thermal responses of alloy and NiTi alloy;
[0047] Figure 7 Copper mold cooling NiTiTa prepared in the embodiment of the present invention 0.2 EBSD characterization images of the alloy at different parts, where (a) is the overall macroscopic morphology; (b) is the microstructure at the top of the sample; (c) is the microstructure at the bottom of the sample; (d) is the microstructure in the middle of the sample; and (e) is the legend.
[0048] Figure 8 Copper mold cooling NiTiTa prepared in the embodiment of the present invention 0.2 Mechanical properties curve of alloy;
[0049] Fig. 9 The diagram is a comparison of the optical protection effects of the multifunctional fusion alloy prepared in the embodiment of the present invention under different conditions, wherein (a) is asymmetric energy deflection; and (b) is complete protection. DETAILED DESCRIPTION
[0050] The technical solution of the present invention is further described below by means of the accompanying drawings and embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any other changes, modifications, substitutions, combinations, simplifications made without violating the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application and belong to the scope of protection of the present invention.
[0051] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.
[0052] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.
[0053] Unless otherwise specified in the present invention, the reagents, instruments, and equipment used are those commonly used by technicians in this field.
[0054] Example
[0055] This embodiment provides a method for preparing a multifunctional fusion alloy of force, heat and light, and the flow chart is as follows: Figure 1 , the specific steps are as follows:
[0056] Ni, Ti, and Ta alloys with a purity higher than 99.9% were mixed in an atomic ratio of 1:1:0.2 and melted five times in an argon atmosphere in a vacuum arc melting furnace, during which the melt was stirred by magnetic drive to obtain a NiTiTa alloy. 0.2 The cast NiTiTa 0.2 The alloy was melted in a nitrogen environment and rapidly solidified in a water-cooled copper mold to obtain an ultrafine grain microstructure. The horseshoe-shaped supersurface array was machined on the alloy surface using FIB technology. 0.2 The bottom layer of the alloy substrate is bonded with a borate cross-linked hydrogel, and the water molecule content of the hydrogel is 70%.
[0057] X-ray diffraction (XRD), differential scanning calorimetry (DSC), electron backscatter diffraction (EBSD), and transmission electron microscopy (TEM) were used to analyze the martensitic phase transformation behavior and test its thermal response. The optical reflectance spectrum was used to determine how the light reflectivity changes with temperature and thermal phase transformation, and the optical regulation capability was evaluated. The tensile strength and deformation recovery rate were tested with the help of a mechanical properties tester.
[0058] Ultrafine-grained NiTiTa was obtained by rapid directional solidification in a water-cooled copper mold. 0.2 The overall morphology of the alloy is shown in Figure 2 As shown in the microscopic morphology Figure 3 As shown in the figure, NiTi Ta 0.2 The alloy consists of a dense microstructure and no voids caused by rapid solidification were found.
[0059] The horseshoe-shaped metasurface array was processed on the alloy surface using FIB technology. The morphology is shown in the figure. Figure 4 As shown. NiTiTa 0.2 The composite interface characterization diagram of the alloy substrate bottom layer and the heat-insulating and heat-absorbing water gel is shown in the figure. Figure 5 As shown in the figure, the two materials can be well composited and the connection interface meets the requirements of contact heat transfer.
[0060] Using Differential Scanning Calorimetry to Test Copper Mold Cooled NiTiTa 0.2 The thermal response of alloy and NiTi alloy is compared with the DSC curve. Figure 6 As shown in the figure, NiTiTa 0.2 The alloy has a lower phase transition temperature, which helps it adapt to extreme environments.
[0061] Analysis of NiTiTa Cooled by Copper Mold Using Electron Backscatter Diffraction 0.2 Basic microstructure information of alloy, copper mold cooled NiTiTa 0.2 EBSD characterization images of the alloy at different locations are shown below: Figure 7 As shown in the figure, the microstructure is relatively uniform, without significant abnormal grains, avoiding local instability of mechanical properties.
[0062] Testing NiTiTa with copper mold cooling using a universal mechanical testing machine 0.2 The alloy yield strength, tensile strength and deformation recovery rate, mechanical properties diagram as shown in Figure 8 As shown. Figure 8 As shown, the yield strength at room temperature is 450MPa, the ultimate tensile strength is 800MPa, and the deformation recovery rate is 100%. Figure 6 The DSD curve of NiTiTa 0.2 The alloy has remarkable shape memory characteristics.
[0063] The optical reflectance of the obtained multifunctional fusion alloy was measured by optical reflectance spectrum with the change of temperature and thermal phase change. Fig. 9 As shown. Fig. 9 It can be seen that the symmetrical propagation characteristics of the optical path realize dynamic regulation of asymmetry.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a multifunctional fusion alloy of power, heat and light, characterized in that: The specific steps include: S1. Mix metal elements Ni, Ti and Ta; S2, the Ni, Ti, Ta metal elements in S1 are placed in a vacuum arc melting furnace for melting to obtain cast NiTiTa 0.2 alloy; S3, the cast NiTiTa obtained in S2 0.2 The alloy is melted and then directionally solidified using a water-cooled copper module to obtain ultra-fine-grained NiTiTa 0.2 alloy; S4, NiTiTa obtained in S3 by FIB technology 0.2 A horseshoe-shaped metasurface with a matrix etched on the alloy; S5, NiTiTa obtained in S4 0.2 The base layer of the alloy is compounded with the heat-insulating and heat-absorbing water gel to obtain a multifunctional fusion alloy.
2. The method for preparing a mechanical, thermal and optical multifunctional fusion alloy according to claim 1, characterized in that: In S1, the atomic ratio of the metal elements Ni, Ti and Ta is 1:1:0.2, and the purity of Ni, Ti and Ta is greater than 99.9%.
3. The method for preparing a mechanical, thermal and optical multifunctional fusion alloy according to claim 1, characterized in that: In S2, Ni, Ti, and Ta metal single substances are melted in an argon atmosphere, and the melt is stirred by magnetic drive.
4. The method for preparing a mechanical, thermal and optical multifunctional fusion alloy according to claim 1, characterized in that: In S3, cast NiTiTa 0.2 The alloy was melted in an argon atmosphere.
5. The method for preparing a mechanical, thermal and optical multifunctional fusion alloy according to claim 1, characterized in that: In S4, the opening angle of the horseshoe is 20-60°.
6. The method for preparing a mechanical, thermal and optical multifunctional fusion alloy according to claim 1, characterized in that: In S4, the matrix array consists of 10×10 horseshoe-shaped units, the diameter of the horseshoe-shaped unit is 500 nm, the opening width is 100-500 nm, and the spacing between adjacent horseshoe-shaped units is 1000 nm.
7. The method for preparing a mechanical, thermal and optical multifunctional fusion alloy according to claim 1, characterized in that: In S5, the heat insulating and heat absorbing hydrogel is a borate cross-linked hydrogel.
8. The method for preparing a mechanical, thermal and optical multifunctional fusion alloy according to claim 1, characterized in that: In S5, the content of water molecules in the heat-insulating and heat-absorbing water gel is 70%.